Toward safe dental service: risk perception and practice modification among Egyptian dental students during the COVID-19 pandemic - Eman Ali Younis; Abdel Aziz farouk El deep; Safynaz El Saied Shalaby; Sanaa Abd El-Fatah Abdo (BMC, 2023)
Abstract Background COVID-19 was declared a major public health crisis and a challenge to healthcare systems especially dental services where dentists working close to patients face a greater risk of infection. This cross-sectional study aimed to assess the risk perception and practice modifications of undergraduate dental students at Tanta University to ensure safe dental practice during the COVID-19 pandemic. Methods A convenience sample of 450 dental students from practical academic years at Tanta University, Egypt responded to a self-administered pre-designed validated and pretested questionnaire from the 11th of February 2022 to the end of April 2022 to assess some sociodemographic data, risk perception, and their practice during the COVID-19 pandemic. Results Females reported significantly higher levels of fear than males concerning; contracting COVID-19 infection from patients (97.3% vs. 93%) (P = 0.028, 95% CI = 95.6(93.2-97.3), anxiety while treating symptomatic patients (95.1% vs. 90.3%) (P = 0.050, 95% CI = 93.1(90.4-95.3), and fear of infecting their families (94.7% vs. 89.8%) (P = 0.049, 95% CI = 92.7(89.9-94.9). More than half of the students (53.7%) had good practice scores, followed by 44% with average practice and 2.2% with poor practice. A good practice score was significantly associated with the age and academic year (P = 0.044, P = 0.044). Significant predictors of a good practice score in the logistic regression analysis were; updating knowledge with current guidelines for cross-infection regarding COVID-19 (P = 0.001, 95% CI = 53.20, 2.733), asking every patient's travel history before performing treatment (P = 0.021, 95% CI = 21.149, 1.286), deferring patients showing suspicious symptoms (P = 0.042, 95% CI = 20.688, 1.054), following routine universal precautions of infection for every patient (P = 0.016, 95% CI = 36.469, 1.438), using high-volume suction for every patient (P = 0.025, 95% CI = 20.826, 1.226) and using safety glasses or visor (P = 0.036, 95% CI = 21.673, 1.106). Conclusion The dental students exhibited anxiety and fear while caring for patients during the COVID-19 pandemic. Additionally, considerable changes in dental practices based on the standard guidelines were observed among the students. It is strongly advised that all dental schools have student counselors who are accessible for in-person and online counseling sessions. Peer support is a great approach to spot problems with stress and anxiety in pupils and start solving them.